CREATION AND PHARMACOTECHNOLOGICAL INVESTIGATIONS OF INNOVATIVE DOSAGE FORMS OF MEXIDOL - E. F. Stepanova; S. O. Losenkova; Yu. A. Morozov (Разработка и регистрация лекарственных средств)
The present study is devoted to the creation and study of transdermal dosage forms with mexidol and experimental substantiation of their therapeutic efficacy. The original technological scheme of production of one of the most popular structures transdermal - transdermal patches with mexidol. Selected efficient packaging, a shelf life of dosage forms. Developed, justified, biopharmaceutical research confirmed the optimal composition cohesive mass. Conducted optimal standardization of patches according to the most characteristic and important indicators. Studied local irritating effect and hipersensitivity proposed dosage form. Investigated and confirmed the ability of transdermal forms of mexidol to percutaneous transport.